PENGOPTIMALAN DISTRIBUSI AIR BERSIH MENGGUNAKAN METODE TRANSPORTASI PADA PERUSAHAAN DAERAH AIR MINUM (PDAM) TIRTA DHARMA KOTA MALANG - Windriya Dhayita Suwandahagni Kurniadi (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2019)
The increase in the population of Malang City has an impact on increasing customers of PDAM Tirta Dharma Malang. The increase in the number of customers affects increasing the amount of clean water usage. The amount of water usage continues to increase opposite to the decline of clean water availability. Clean water in nature decreases due to pollution, population density, and land-use change. Clean water supply efforts are needed to overcome this problem. Improving water distribution services is needed to meet the demand for water requirements and minimized distribution costs. The right method for determining the optimal distribution cost is the transportation method. The methods used in this research are the Northwest Corner Method, Least Cost Method and Vogel’s Approximation Method also used Modified Distribution to find the optimal solution. The calculation result obtained, the minimum operational cost is Rp49.010.842,00 per day. It is lower than the previous operational cost. The previous operational cost is Rp54.698.296,00 per day.